The Impact of Utilizing Artificial Intelligence in Human Resource Management on the Quality of Administrative Decisions and the Sustainability of Institutional Performance: An Applied Study at Erbil Investment and Finance Bank - Yousif Riyadh Mhmood; Rawad Fadhil Abed Alabboodi; Ashwaq Thabit Abed (Jurnal Akuntansi, Manajemen, dan Perencanaan Kebijakan, 2026)
The research aims to study effect employment Technologies intelligence artificial in administration Resources Humanity on quality Decisions Administrative sustainability Performance Institutional, That's from during application field in bank Erbil For investment and the funding. and it started. the study from hypothesis Its meaning that Use Applications intelligence artificial in Jobs Resources Humanity Contributes in Strengthening efficiencyOperations Administrative, and improving accuracy and speed Decisions, and support investigation performance Founders Sustainable. Adopted, Search Curriculum Descriptive Analytical, And it was used questionnaire as a tool President To collect Data from sample from staff in the bank and it was analysis Data Using Methods Statistics The occasion . And it showed results Search presence effect positive This indication Statistics To hire intelligence artificial in administration Resources Humanity on quality Decisions Administrative, as Contributes In a way active in Strengthening Sustainability Performance Institutional. And concluded Search to group from Recommendations, from The most prominent of them necessity Expansion in adoption Technologies and tools intelligenceartificial, As well as development Structure Infrastructure Digital, and qualification Resources Humanity In what It fits with requirements Transformation digital in sector The banker.